Promoting Eco-Pesantren Based on Qur’an and Hadith at PPTA Al-Kamal Integrated Islamic Boarding School, Blitar, East Java, Indonesia - Abidin, Ahmad Zainal; Noorhidayati, Salamah (Institut Agama Islam Negeri (IAIN) Keiri, 2025)
This article aims to analyze how the Living Qur’an and Hadith approach is operationalized in the eco-pesantren at Al-Kamal Integrated Islamic Boarding School (PPTA), Blitar, East Java, Indonesia, and to uncover its contribution to environmental empowerment and the surrounding community. This research employs a qualitative field research method using the Living Qur’an-Hadith approach within the framework of socio-cultural studies. Data were collected through in-depth interviews, participatory observation, and documentation, with research subjects including pesantren leaders, eco-pesantren program managers, and students (santri). The findings reveal the following: first, the basic principles of the eco-pesantren at PPTA are rooted in ecological values found in selected Qur’anic verses (QS al-Baqarah [2]: 30; QS al-A‘rāf [7]: 56; QS al-Qaṣaṣ [28]: 77) and prophetic traditions that emphasize human vicegerency, the prohibition of environmental destruction, and cleanliness as part of faith. Second, these principles are implemented through sanitation programs (clean water provision, hygiene facilities, and a health post) and a waste bank system involving waste sorting and utilization of both organic and inorganic waste. Third, the eco-pesantren not only impacts the pesantren internally but also generates economic and social benefits for the surrounding community, such as utilizing food waste for livestock feed and generating income from plastic waste. This study demonstrates that the application of ecological principles from the Qur’an and Hadith through the eco-pesantren concept at PPTA has a significant impact on environmental awareness and community well-being, while enriching the study of the Qur’an and Hadith within the context of contextual social practices.